Discovery and Optimization of Tau Targeted Protein Degraders Enabled by Patient Induced Pluripotent Stem Cells-Derived Neuronal Models of Tauopathy - Silva, M. Catarina; Nandi, Ghata; Donovan, Katherine A.; Cai, Quan; Berry, Bethany C.; Nowak, Radoslaw P.; Fischer, Eric S.; Gray, Nathanael S.; Ferguson, Fleur M.; Haggarty, Stephen J. (Frontiers in Cellular Neuroscience, 2022)
Accumulation of misfolded, aggregating proteins concurrent with disease onset and progression is a hallmark of neurodegenerative proteinopathies. An important class of these are tauopathies, such as frontotemporal dementia (FTD) and Alzheimer’s disease (AD), associated with accumulation of aberrant forms of tau protein in the brain. Pathological tau undergoes abnormal post-translational modifications, misfolding, oligomerization and changes in solubility, cellular redistribution, and spreading. Development and testing of experimental therapeutics that target these pathological tau conformers requires use of cellular models that recapitulate neuronal endogenous, non-heterologous tau expression under genomic and physiological contexts relevant to disease. In this study, we employed FTD-patient induced pluripotent stem cells (iPSC)-derived neurons, expressing a tau variant or mutation, as primary models for driving a medicinal chemistry campaign around tau targeting degrader series. Our screening goal was to establish structure-activity relationships (SAR) for the different chemical series to identify the molecular composition that most efficiently led to tau degradation in human FTD ex vivo neurons. We describe the identification of the lead compound QC-01-175 and follow-up optimization strategies for this molecule. We present three final lead molecules with tau degradation activity in mutant neurons, which establishes potential disease relevance and will drive future studies on specificity and pharmacological properties.